RETRACTED: How Does Environmental Regulation Affect Green Innovation? A Perspective From the Heterogeneity in Environmental Regulations and Pollutants - Chen, Zhenling; Niu, Xiaoyan; Gao, Xiaofang; Chen, Huihui (Frontiers in Energy Research, 2022)
Green (technical) innovation is expected to be an effective tool for addressing environmental crises. However, the effect of environmental regulations on green innovation may depend on the type of environmental regulation. To that end, this study utilizes panel data covering 30 Chinese provinces to explore the mechanism underlying the relationship between these two variables in light of the heterogeneity in environmental regulations and pollutants. The direct effects of three types of environmental regulations and four pollutants are verified, as are the thresholds in the effects of environmental regulation on green innovation. The results show that 1) both market-incentive and public participation-based environmental regulations have positive effects on green innovation, while command-and-control regulations do not. Unlike the effects of the market-incentive tool, which has a single threshold, the effect of public participation-based environmental regulations has two thresholds, which indicates that there is too little public participation for such regulations to be effective and too much for them to be sensitive to environmental protection. 2) Three of the four pollutants (industrial wastewater, waste gas, and carbon emissions) have a significantly positive impact on green innovation only when they exceed the first threshold value, whereas an increase in industrial solid waste has little effect on green innovation until it exceeds the second threshold value. 3) In the eastern region, all three kinds of environmental regulations play a significant role in promoting green innovation, and their effects are greater than those in the western region. However, the effect of environmental regulation in the central region is not different from that in the western region.